2021
DOI: 10.3390/biology10080794
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Prevalence of High-Risk HPV Genotypes Other than HPV-16 and HPV-18 among Women Attending Gynecologists’ Offices in Kazakhstan

Abstract: Cervical cancer represents a great burden to public health of women. This study aimed to obtain a nationwide genotyping survey and analysis of high risk-HPV including those that are caused by HPV types other than HPV-16 and HPV-18, among women in Kazakhstan. This study was conducted based on the collection of survey and cervical swabs of 1645 women across the country. The samples were genotyped for high-risk HPV types based on real-time PCR methods. Collected data was analyzed with the focus on high-risk HPV t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…4 Earlier pilot studies reported the prevalence of high-risk HPV in Western Kazakhstan 5 and the capital city Astana. 6 More recent regional studies on HPV prevalence among Kazakhstani women reported high-risk HPV infection in 39% of study participants, 7,8 which in turn leads to a high incidence of cervical cancer. 9,10 In 2020, there were 1,777 cases of cervical cancer and 834 related deaths in Kazakhstan, with the crude incidence rate among females equal to 18.4 per 100,000 population.…”
Section: Introductionmentioning
confidence: 99%
“…4 Earlier pilot studies reported the prevalence of high-risk HPV in Western Kazakhstan 5 and the capital city Astana. 6 More recent regional studies on HPV prevalence among Kazakhstani women reported high-risk HPV infection in 39% of study participants, 7,8 which in turn leads to a high incidence of cervical cancer. 9,10 In 2020, there were 1,777 cases of cervical cancer and 834 related deaths in Kazakhstan, with the crude incidence rate among females equal to 18.4 per 100,000 population.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this is the first study that aimed to examine attitudes toward HPV vaccination and explore factors associated with a positive attitude toward HPV vaccination in Kazakhstani women. Since HR-HPV prevalence is high among women in Kazakhstan [ 13 , 14 , 15 , 21 ], and cervical cancer incidence has increased in the past decade [ 16 ], becoming the fourth leading cause of death from cancer among women [ 35 ], it is important to implement primary prevention of HPV infection and its related diseases in the country. However, the successful relaunching of the HPV vaccination program largely depends on HPV vaccine attitudes; therefore, studies investigating society’s attitudes towards the vaccine are an essential part of facilitating the process.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest prevalence of HPV infection is reported in Middle Eastern and North African countries (7–16%) [ 12 ]. According to the available epidemiological data, HR-HPV prevalence in Kazakhstan is high among women attending gynecological offices, ranging from 39% to 43% [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, more than 99% of cervical cancer patients are positive for one or more highly oncogenic HPVs. Among the 12 highly oncogenic HPV types, HPV-16 and -18 are the most prevalent subtypes worldwide and are responsible for up to 70% of cervical cancer cases ( 4 ). Because HPV is primarily a precursor for the development of cervical cancer, any effort to help understand the oncogenic impact of HPV or prioritize HPV-based innovative treatment strategies (i.e., host-oriented drug targets) will transform and advance bioscience research and the bioscience industry.…”
Section: Introductionmentioning
confidence: 99%